MENINGKATKAN KARAKTER KEJUJURAN MELALUI PEMBELAJARAN BERBASIS PENGALAMAN KONKRET PADA SISWA KELAS VI SD NEGERI NO. 100102 PANOBASAN - Rosmanila Lubis; Nahriyah Fata; Nahdah Faizah Harahap (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This Classroom Action Research (CAR) aims to improve the honest character of sixth-grade students of SD Negeri No. 100102 Panobasan through concrete experience-based learning. This research is motivated by students' low level of honesty in daily activities, both inside and outside the classroom. The research method uses the Kemmis and McTaggart model, which consists of two cycles of planning, implementation, observation, and reflection. Each cycle involves learning activities designed to provide concrete experiences, such as simulations, role plays, and group discussions related to real-life situations that require honesty. The results of the study showed a significant increase in the honest character of students after the implementation of concrete experience-based learning. This is shown through observations of student behavior, reflection results, and positive responses from teachers and students. The percentage of student honesty increased from 60% in the first cycle to 85% in the second cycle. In conclusion, concrete experience-based learning effectively instills honesty values in students. This study recommends using a similar approach in learning other character values